Optimization of low frequency noise for dielectric modulated TFET for bio sensing applications. Issue 1 (February 2021) - Bhattacherjee, S.; Roy, S.; Chakroborty, G.; Ray, U.
Abstract: In this paper first time we are working on the low frequency noise analysis of dielectric modulated TFET biosensors. Our work is based on simulation technique using SILVACO ATLAS. We used different dielectrics in order to detect biomolecules. Moreover we also observed the drain current power spectral density relevant to low frequency noise of the biosensor. Our results show that noise has a significant role and it depends on the insulating layers of the dielectric modulated biosensor. Thus the application of suitable dielectric material can effectively improve the optimum performance of the dielectric modulated biosensor.